Effect of anesthesia type on outcome measures in cesarean section in the presence of fetal macrosomia - Taşgöz,Fatma Nurgül (2022)
SUMMARY OBJECTIVE: The aim of this study was to compare the effects of general and spinal anesthesia on maternal and neonatal outcomes during cesarean section in pregnancies with macrosomia. METHODS: This retrospective cohort study included 1043 patients who delivered by cesarean section between May 2018 and December 2021 and had a baby born with a birth weight of 4000 g or greater. Maternal and neonatal outcomes were compared according to the type of anesthesia performed in the spinal anesthesia group (n=903; 86.6%) and general anesthesia group (n=140; 13.4%). The Apgar score was categorized into <7 and ≥7. RESULTS: Neonates with an Apgar score of <7 at the first minute (11.4 vs. 0.4%; p<0.001) and the fifth minute (2.9 vs. 0.3%; p=0.004) were significantly higher in the general anesthesia group. The preoperative and postoperative hematocrit difference was significantly lower in patients who received spinal anesthesia than those who received general anesthesia [2 (1.1–3.1) vs. 4.05 (2.8–5.35); p<0.001]. The number of patients transfused was higher in the general anesthesia group (9.3 vs. 2.7%; p<0.001). In the regression model, general anesthesia, birth weight, and emergency conditions were significant independent factors related to the preoperative and postoperative hematocrit decrease (p<0.001, p=0.005, and p=0.034, respectively). CONCLUSIONS: Apgar scores of <7 at the first and fifth minutes are higher in macrosomic neonates who received general anesthesia than in neonates who received spinal anesthesia. Performing cesarean section under general anesthesia in mothers of macrosomic neonates results in a greater decrease in hematocrit value and a greater need for blood transfusion than under spinal anesthesia.